How Do Diet Patterns, Single Foods, Prebiotics and Probiotics Impact Gut Microbiota? - Andrea Piccioni; Marcello Covino; Marcello Candelli; Veronica Ojetti; Annunziata Capacci; Antonio Gasbarrini; Francesco Franceschi; Giuseppe Merra (Microbiology Research, 2023)
The human gastrointestinal tract hosts a complex and dynamic population of commensal bacterial species, which have coevolved with the host, generating a symbiotic relationship. Some compounds present in foods, such as polyols, prebiotic fibers, or phenolic compounds, are poorly metabolized and absorbed by the host before the transformation guided by the colonic microbiota. By influencing gut microbiota, diet plays a fundamental role in understanding the beneficial effects of the gut microbiota on the host, including its long-term metabolism. The idea that probiotics can act not only by influencing the colonizing microbiota opens the door to a wider range of probiotic possibilities, encouraging innovation in the field. Furthermore, it has been shown both that some probiotics increase phagocytosis or the activity of natural killer cells. Current prebiotics are mainly based on carbohydrates, but other substances, such as polyphenols and polyunsaturated fatty acids, could exert prebiotic effects. A prebiotic substance has been defined as ‘a substrate that is selectively used by host microorganisms that confer a health benefit’, and so can interact with the gut microbiota through competition for nutrients, antagonism, cross-feeding, and support for microbiota stability. Influencing its composition in terms of richness and diversity, food components have a key impact on the intestinal microbiota. Eating habits can strongly influence the composition of the intestinal microbiota. A healthy intestinal microbiota is essential for maintaining general health, and diet is one of the major modulators of this fascinating world of microorganisms. This must give us one more reason to adopt a healthy lifestyle.